Efeitos de localização de portadores em poços quânticos de GaBiAs/GaAs - Carvalho, Anne Rose Hermanson (2015)
In order to investigate optical and spin properties of GaBiAs / GaAs quantum wells, we performed both photoluminescence and magneto-photoluminescence spectroscopy measurements in three samples: 10 nm quantum wells with Bi concentrations of 1%, 2% and 3%. The photoluminescence study was conducted as a function of Bi concentration, temperature and excitation power. The results indicate that the effects associated with carrier localization by defects are expressive, especially for the 3% sample. The defects are incorporated into the solid due to growth conditions at low temperatures (315 °C), necessary to enable Bi incorporation into the GaAs matrix.They are also due to the different properties between the atoms, such as electronegativity and size. The magneto-luminescence results exibited high spin- splitting (8.4 meV to 15 T) and high excitonic g factor (9.6) for the 3% sample. It also showed a small diamagnetic shift (approximately 3 meV) for the three samples and moreover, it decreases with increasing Bi content. This suggests higher carrier localization by defects, confirming previous results. Overall, the results show that such materials are interesting and good candidates for spintronic applications.